Professional training... total action. (Journal of Parents and Teachers, 2014)
The educational option is divided into two tracks in its highest stages: academic training in the university and vocational training. This article reflects on the results of vocational training, its structure and contents while offering tables with data on the different economic sectors and educational laws.
Keywords: Academic training; professional training; implications; conclusions; results; economic sectors; educational laws.